PENGARUH CAMEL TERHADAP RETURN SAHAM YANG TERDAFTAR PADA BANK UMUM SWASTA NASIONAL PADA BEI PERIODE 2012-2014 - Resti Honora; Makhdalena '; R.M.Riadi ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: To assess the stock returns are many factors that can be used as a parameter, from a variety of factors, among others, the company's financial information obtained reflected by financial ratios. Financial ratio analysis is an analytical instrument company that explains the changes in the financial condition or operations of the past achievements and help illustrate the change to later demonstrate the opportunities and risks in the company concerned. Financial ratios are basically prepared by combining the figures in the financial statements. Financial ratios become one of the decision makers for both internal and external parties, especially creditors and investors, financial ratios can be used in determining whether a reasonable company to be granted credit or to clear land for a good investment. The purpose of this study was to determine whether there is influence on stock returns CAMEL. The method used in this research is descriptive quantitative manner mendeskriptifkan research variables include CAR (Capital Adequacy Ratio), NPL (Non Performing Loan), ROA (Operating Expenses Against Operating Income), ROA (Return on Assets), LDR (Loan To Deposit Ratio) and Stock Return sourced the data from the Indonesian Stock Exchange (IDX). Based on the financial statements will be calculated a number of financial ratios commonly used as the basis of assessment of the bank. Based on the results of the regression analysis, simultaneously, CAR, NPLs, ROA, ROA, and LDR significant effect on stock return of 32.2% while the remaining 67.8% are influenced by variables that are not observed in this study model, but partially ROA and ROA are variables that significantly affect the Stock Return whereas other variables namely CAR, NPL, and LDR is not significant.Keywords: CAR,NPL,BOPO,ROA,LDR,Return Saham